Pengoptimalan Lahan Pekarangan Sebagai Upaya Ketahanan Pangan Pada Kawasan Rumah Pangan Lestari - Robby Sandhi Dessyarti; Apriyanti Apriyanti; Metik Asmike; Novi Dwi Lestari; Risma Choirunisa (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2022)
Abstract: Klangon Village is a hilly area which is located on the slopes of Mount Pan-dan and is in the Madiun Regency area which is one of the partner villages of Universitas PGRI Madiun. Klangon Village has an organization in the field of agriculture, namely the “Karya Putri Tani” farmer group. The organization received funding aimed at the development of a sustainable food housing area (KRPL) but it was not yet optimal and running smoothly. The existence of these problems became the basis for conducting yard optimization activities for food security in the area of sustainable food houses. The methods used in the activities include mentoring and training in the form of demonstrations. Hope in this program can meet the needs, food security, and nutrition of the family which will ultimately improve the welfare of the community. The results achieved in the program are that the target group can implement a sustainable food home area in the form of "Green House Klangon" as an educational tool.       Keywords: optimization; accompaniment; krpl programmeAbstrak: Desa Klangon merupakan daerah perbukitan yang letaknya di lereng Gunung Pandan serta berada di wilayah Kabupaten Madiun dimana menjadi salah satu desa mitra Universitas PGRI Madiun. Desa Klangon memiliki organisasi dibidang pertanian yaitu kelompok tani “Karya Putri Tani”. Organisasi tersebut memperoleh pendanaan yang ditujukan untuk pembangunan kawasan rumah pangan lestari (KRPL) namun belum optimal dan berjalan lancar. Adanya permasalahan tersebut menjadi dasar diadakan kegiatan pengoptimalan lahan pekarangan sebagai upaya ketahanan pangan pada kawasan rumah pangan lestari. Metode yang digunakan dalam kegiatan mencakup pendampingan dan pelatihan berupa demontrasi. Harapan dalam program ini dapat memenuhi kebutuhan, ketahanan pangan dan gizi keluarga yang pada akhirnya akan meningkatkan kesejahteraan masyarakat. Hasil yang dicapai dalam program yaitu kelompok sasaran dapat mengimplementasikan kawasan rumah pangan lestari dengan wujud “Green House Klangon” sebagai sarana edukatif.Kata kunci: optimalisasi; pendampingan; program krpl